Writing research & thesis proposals guidelines & examples - Noorzan Mohd Noor (Penerbit Universiti Teknologi Mara, 2010)
This text is intended to be an aid for anyone wishing to write research or thesis proposals. It provides the essential elements, tips and examples on preparing, organizing and writing a research proposal.